Continuous input of organic ultraviolet filters and benzothiazoles threatens the surface water and sediment of two major rivers in the Pearl River Basin - Hu, Li-Xin; Cheng, Yu-Xiao; Wu, Dan; Fan, Lei; Zhao, Jia-Hui; Xiong, Qian; Chen, Quan-Le; Liu, You-Sheng; Ying, Guang-Guo (The Science of the total environment, 2021)
The extensive usage of organic ultraviolet filters (UV filters) and benzothiazoles (BTs) has caused continuous and widespread pollution in the aquatic environment. This study investigated the occurrence of nine organic UV filters and eight BTs in the surface water and sediment of two major drinking water source rivers in the Pearl River Basin (PRB). The detection frequencies of six organic UV filters and seven BTs were above 50% in surface water, while eight target compounds were as high as 100%. Composition profiles revealed that 2-Hydroxybenzothiazole (2-OH-BTH, 1112 ng/L) and 2-Mercaptobenzothiazole (2-SH-BTH, 426.3 ng/L) were the predominant compounds in surface water, while Octyl 4-methoxycinnamate (OMC, maximum concentration, 68.3 ng/g) and UV-329 (18.8 ng/g) were predominant in sediment. Significant positive correlations were observed between water quality parameters (temperature, total phosphorus (TP) and total nitrogen (TN)) and organic UV filters (UV-327 and UV-P), indicating the domestic discharge. The calculated annual flux of targets compounds indicated that West River (WR) promoted more BTs and UV filters to the PRB than North River (NR) (BTs: WR22, 88,517 kg/year; NR13, 15,660 kg/year; UV filters: WR22, 28,332 kg/year; NR13, 1128 kg/year). Significant relationship between the Gross Domestic Product (GDP) and annual flux of BTs (R2 = 0.96, p < 0.001), and UV filters (R2 = 0.88, p < 0.001) in the rivers were found by regression analysis. UV-329 was detected with medium risk (RQ > 0.1) in all WR surface water samples, and 2-SH-BTH was detected with high risk (RQ > 1) in half of the WR sediment samples. This study provides the first time reports on the organic UV filters and BTs in two major rivers in the Pearl River Basin, and further showed that these two types of contaminants are ubiquitous and with potential risks in surface water and sediment of PRB. [Display omitted] •10 UV filters and 13 BTs in two drinking water source rivers were investigated.•A total of 17 targets were detected in water from the Pearl River Basin (PRB).•2-OH-BTH and OMC were the predominant targets in surface water and sediment.•Annual flux of UV filters and BTs in the rivers significantly correlated with GDP.•Typical UV filters and BTs pose a potential ecological risk in rivers of PRB.